Development of Local Original Income Potential (PAD) in Magelang City with System Parking Subscribe - Mirajhusnita, Isradias; Yunus, Muhamad; Yunita, Sisca Ratna (Universitas Pancasakti Tegal, 2024)
The Magelang City Government increases its Regional Original Income through parking fees in line with increasing need for provision of supporting facilities needed by the community. Magelang City has a land area of around 18.12 km² with an average population growth from 2017- 2020 as big as 3%. By Because That, Magelang City need arrangement parking Which effective And efficient. Studies This aims to compile and analyze parking management strategies that have an impact on increasing PAD Magelang City. Location studies implemented in 11 block parking Magelang City with using method quantitative descriptive research source the data came from secondary data. The analysis that done use comparison between System For Results And System Parking Subscribe. Results analysis shows that parking fee income with the Subscription Parking System has potential value which is better in increasing the Original Regional Income of Magelang City compared to the Revenue Sharing System. Results.